Anomalous systemic arterial supply to the left lower lung lobe: A case report - Wu, Zhuo; Xu, Baoning; Zhou, Di; Yang, Xueying (Frontiers in Medicine, 2022)
Background An anomalous systemic arterial supply to the lung lobes is a rare congenital pulmonary vascular malformation. Current treatments include thoracoscopic lobectomy, anatomical segmentectomy, simple ligation and arterial embolization. However, the optimal treatment remains controversial. Case presentation A 29-year-old man was diagnosed with anomalous systemic arterial supply to the left lower lobe through contrast-enhanced computed tomography and three-dimensional reconstruction. He underwent coil embolization of the anomalous artery and was followed up for 1 year. Conclusions Blockage of the blood flow of the anomalous systemic artery alone does not improve the blood supply of the pulmonary artery to lung tissue and thus cannot restore normal gas exchange through the blood-gas barrier. Coil embolization of the anomalous arterial supply can cause early postoperative pulmonary infarction.